Superhydrophobicity of AA2024 by a simple solution immersion technique. Issue 4 (1st December 2013) - Lakshmi, R. V.; Bharathidasan, T.; Basu, Bharathibai J.
Abstract : Superhydrophobic films with hierarchical structures were fabricated on AA2024 alloy by a simple solution immersion technique comprising surface pretreatment by alkaline etching and immersion in an ethanolic solution of long-chain fatty acid. The etched surface was hydrophobically modified using alkanoic acids. The effect of etchant concentration and carbon chain lengths of alkanoic acids on WCA of the alloy surface was studied. Field emission scanning electron microscopy, energy dispersive spectrometer and water contact angle measurements were performed to characterize the morphological features, chemical composition and wettability of the surfaces. The resulting superhydrophobic surfaces exhibited water contact angles of about 157° and sliding angle <2°. Surface modification with fluoroalkylsilane also rendered superhydrophobicity to the etched surfaces. The wettability behavior of the superhydrophobic surface was correlated to surface roughness using Cassie-Baxter model.